Canadian Journal of Kidney Health and Disease: A Unique Launch of a Unique Journal. Issue 1 (7th April 2014) - Levin, Adeera; Clase, Catherine M; Sood, Manish M; Dicks, Elizabeth; Fortin, Marie-Chantal; Hartwig, Sunny; Holden, Rachel; Lafrance, Jean-Philippe; Molzahn, Anita; Rosenblum, Norman; Samuel, Susan; Soroka, Steven
Usually inaugural editorials are written by the Editor-in-Chief to describe the scope and vision for the journal to potential authors and readers. This editorial is written by the Editor-in-Chief, the Deputy Editors and the Associate Editors collaboratively as a clear signal that this is a unique and different journal. We will build this journal on a set of principles which are fundamental to improving the outcomes of patients with kidney disease. To that end, we aim to be supportive, to collaborate, to integrate multiple perspectives and to be open to possibilities.